Mechano‐Hydrolysis of Non‐Conventional Substrates for Biofuel Culture Media - Juárez Arellano, Erick Adrián; Morales Toledo, Lizzette Ivette; Martínez-López, Valeria; Urzúa Valenzuela, Michell; Aparicio Saguilan, Alejandro; Navarro Martinez, Ana Karin (Starch - Stärke, 2019)
One of the most crucial steps in the bioconversion of biomass to biofuels is the biomass pretreatment. Here, the use of high-energy ball-milling as a one-step treatment method for fast production of fermentable sugars from starch sources as tubercles (Colocasia esculenta (taro), Colocasia antiquorum (islander), and Manihot esculenta (cassava)) is explored. The results indicate that the maximum reducing sugar concentration is obtained after 20 min (taro and islander) or 30 min (cassava) of milling. Compared with untreated samples the reducing sugar concentration increases 1.5 times in cassava, 4.5 times in islander, and 4.8 times in taro. No fermentation inhibitors or by-products are generated during the physical treatment. The milled samples have been used in the growth media of a model microorganism like Escherichia coliEscherichia coli. The E. coli growth yield using islander milled 20 min is 31 times higher than dextrose. Finally, a mechanism of the effect of high-energy ball-milling treatment on the physicochemical properties of starch-rich biomass is proposed.
Keywords: Molienda energética; Azúcares fermentables; Biomasa amilácea